SUN TOLERANCE AND PHYSIOLOGICAL PARAMETERS OF GOATS GRAZING PANICUM MAXIMUM CV. TOBIATA - Marques, R. O. [UNESP]; Goncalves, H. C. [UNESP]; Meirelles, P. R. L. [UNESP]; Lourencon, R. V. [UNESP]; Oliveira, G. M. [UNESP]; Martins, M. F. [UNESP]; Gomes, H. F. B.; Canizares, G. I. L. [UNESP]; Brito, E. P. [UNESP]; Correa, H. L. [UNESP] (Inst Zootecnia, 2018)
The aim of this study was to evaluate the influence of supplementation on sun tolerance and physiological parameters of goats in grazing. Sixty goats (20 Alpine, 18 Anglo-Nubian and 22 crossbred Boer) primiparous and multiparous, with average body weight of 49.33 +/- 1.41 kg were used in this experiment. The goats were kept in rotational pastures of Panicum maximum cv. Tobiata and supplemented with two levels of concentrate: 300 (NS30) and 600 g/ kg (NS60) of the daily dry matter requirements, assessed from pre-breeding season to approximately 110 days of lactation. Visual observations of tolerance of goats in the sun were made monthly, each 15 minutes during the entire period that the animals remained in the pasture. The respiratory rate and rectal temperature were evaluated monthly, being measured at 9 a.m., 1 p.m. and 5 p.m. Temperature and air relative humidity were recorded every hour, on the days of data collection. Breed influenced the respiratory rate and rectal temperature at 1 p.m., and the crossbred Boer animals showed more appropriate physiological parameters, leading to greater heat tolerance. There was no influence of treatment on the physiological variables of the goats. The Anglo-Nubian goats showed higher resistance to direct sun radiation, staying longer in the sun, being the most suitable for the production system in pasture.
Keywords: caprine; rectal temperature; respiratory frequency; THI